Maximizing restorable load amount for specific substation during system restoration - Qu, Hanbing; Liu, Yutian (International journal of electrical power & energy systems, 2012)
► A mathematical model for calculating the maximum restorable load is presented. ► Transient voltage-dip constraint is analyzed in detail by a fast estimation. ► The ASF model is adopted to calculate the frequency deviation. ► Cold load pickup characteristics are addressed according to a simple guideline. ► A modified bisection method is proposed to solve the complex problem. During power system restoration, the maximum load amount that a substation can pick up at one time is a critical parameter to be determined. Many factors should be considered, such as frequency constraint, transient voltage-dip constraint, steady-state voltage constraint and cold load pickup. This paper proposes a mathematical model for calculating the maximum restorable load amount, in which proper checking methods are presented to deal with these constraints. Frequency deviation is calculated by the average system frequency model. The transient voltage-dip constraint is dealt with by a fast estimation. Cold load pickup characteristics are addressed according to a simple guideline. And a modified bisection algorithm is proposed to solve the complex problem efficiently. The effectiveness is demonstrated by case studies performed on the IEEE 14-bus system and a practical power system.